2020
DOI: 10.3389/fonc.2020.595804
|View full text |Cite
|
Sign up to set email alerts
|

Cancer History and Systemic Anti-Cancer Therapy Independently Predict COVID-19 Mortality: A UK Tertiary Hospital Experience

Abstract: BackgroundThe COVID-19 pandemic remains a pressing concern to patients with cancer as countries enter the second peak of the pandemic and beyond. It remains unclear whether cancer and its treatment contribute an independent risk for mortality in COVID-19.MethodsWe included patients at a London tertiary hospital with laboratory confirmed SARS-CoV-2 infection. All patients with a history of solid cancer were included. Age- and sex-matched patients without cancer were randomly selected. Patients with hematologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 12 publications
2
20
0
Order By: Relevance
“…Previous studies. Despite the large number of studies on prognostic factors for severe COVID-19 [3][4][5][6][7][8][25][26][27][28][29][30][31][32][33][34][35][36] , to our knowledge no previous study has investigated the predictive role of early life events as a risk factor for severe COVID-19 in adulthood. Results confirmed our working hypothesis, which was aligned with a long-standing research line in this field 11,12,18,19,37 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies. Despite the large number of studies on prognostic factors for severe COVID-19 [3][4][5][6][7][8][25][26][27][28][29][30][31][32][33][34][35][36] , to our knowledge no previous study has investigated the predictive role of early life events as a risk factor for severe COVID-19 in adulthood. Results confirmed our working hypothesis, which was aligned with a long-standing research line in this field 11,12,18,19,37 .…”
Section: Discussionmentioning
confidence: 99%
“…Besides, results confirmed previous studies showing a strong predictive value for severe COVID-19 of older age, male sex and coexisting conditions such as hypertension [3][4][5][6][7][8][25][26][27][28][29][30][31] . The fact that we studied non-elderly adults (≤ 70 years) may have limited the identification of significant associations with other reported coexisting conditions such as chronic lung disease 2,[6][7][8]27 , diabetes [2][3][4][5]7,8,25,26,30,32 , obesity 8,31,33 or cancer 3,34 . Current or previous smoking status 35 and chronic treatment with ACE inhibitors 36 were not asso- www.nature.com/scientificreports/ ciated with COVID-19 severity in our dataset.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of anti-cancer treatments are also important factors that influence the risks of infectivity and severity of COVID-19 (36,37). While chemotherapy was shown to be associated with a higher risk of COVID-19 worsening, interestingly patients treated with immune checkpoint immunotherapies or targeted anticancer therapies were not (33,34,(36)(37)(38). Other studies suggested that patients treated for cancer and receiving anti-androgenic treatments or anti-angiogenic drugs could have improved outcomes (39)(40)(41).…”
Section: Covid-19 Pathological Mechanismsmentioning
confidence: 99%
“…In order to find out the impact of COVID-19 infection on the mortality of cancer patients, we conducted an extensive literature search through PUBMED and summarized 13 comparative studies [5][6][7][8][9][10][11][12][13][14][15][16][17] with more than 200 subjects, which compared the mortality of cancer patients versus non-cancer patients infected with COVID-19. Among all studies, 12 of them showed that the death rate of cancer patients with COVID-19 was higher than that of patients without cancer infected with COVID-19, as shown in Figure 1.…”
Section: The Impact Of Covid-19 On Cancer Patientsmentioning
confidence: 99%